Nourishing the future: A collaborative approach to ending undernutrition in Kenya’s ASALs - Kirui, Leonard; Amunga, Dorcas; Mulwa, Chalmers; Mwaura, Lucy; Grant, Fred; Mukani, Moyo; Malit, Jack (International Potato Center, 2024)
Millions of children across Africa, particularly those living in areas plagued by drought and unpredictable weather, constantly struggle to get enough healthy food to thrive. Poor diets can have devastating consequences, leading to stunted growth, increased illness, and even death. In Kenya alone, nearly 1 in 5 children under 5 years suffer from stunting, with this number rising even higher in rural areas [KNBS and ICF, 2023]. But there’s a glimmer of hope. Through collaboration and innovative solutions, communities are charting a path toward a future of food security and improved nutrition.